Sikh News in India, 1864-1924 : Colonial Reports on Vernacular Newspapers of Punjab Volume Two: Religious Places, Practices, and Relations - Myrvold, Kristina, (Asian Studies E-Books Online, Collection 2025., 2025)
This handbook, divided into four volumes, presents the first English translations of newspaper articles about the Sikhs published in the weekly press reports for Punjab between 1864 and 1924. Covering press material from over 300 newspapers, the book provides insights into the broader landscape of print media in Indian languages and how discussions on the Sikhs in the press evolved in response to changing imperial policies and politics. In a growing field of research on print cultures and publics in colonial India, the book offers unique source material for a nuanced and localized understanding of the history of the Sikhs in Punjab. Invaluable to both scholars and students of history, Punjabi society, religion and politics. This is volume 2 of a 4-volume set.